2018
DOI: 10.1093/femsyr/foy085
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated bioprocessing of raw starch with Saccharomyces cerevisiae strains expressing fungal alpha-amylase and glucoamylase combinations

Abstract: Cost-effective consolidated bioprocessing (CBP) of raw starch for biofuel production requires recombinant Saccharomyces cerevisiae strains expressing α-amylases and glucoamylases. Native Aureobasidium pullulans apuA, Aspergillus terreus ateA, Cryptococcus sp. S-2 cryA and Saccharomycopsis fibuligera sfiA genes encoding raw-starch α-amylases were cloned and expressed in the S. cerevisiae Y294 laboratory strain. Recombinant S. cerevisiae Y294[ApuA] and Y294[AteA] strains produced the highest extracellular α-amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The estimated carbon conversion of 85% displayed by the S. cerevisiae Y294[TemG_Opt–TemA] was 31% higher than the Y294[TemG_Opt-AteA] strain, as well as the Y294[AmyA-GlaA] benchmark yeast (Table 2). The Y294[TemG_Opt–TemA] strain also showed an overall improvement in starch conversion to ethanol, compared to the previously constructed Y294[AteA-GlaA] strain [24], which produced 45.80 g l −1 ethanol after 144 h with an estimated carbon conversion of 45%.…”
Section: Resultsmentioning
confidence: 87%
“…The estimated carbon conversion of 85% displayed by the S. cerevisiae Y294[TemG_Opt–TemA] was 31% higher than the Y294[TemG_Opt-AteA] strain, as well as the Y294[AmyA-GlaA] benchmark yeast (Table 2). The Y294[TemG_Opt–TemA] strain also showed an overall improvement in starch conversion to ethanol, compared to the previously constructed Y294[AteA-GlaA] strain [24], which produced 45.80 g l −1 ethanol after 144 h with an estimated carbon conversion of 45%.…”
Section: Resultsmentioning
confidence: 87%
“…However, the CBP applied to starch requires recombinant Saccharomyces cerevisiae strains producing sufficient quantities of raw starch hydrolyzing enzymes to ensure complete hydrolysis at a high substrate loading. This has become the primary focus of several research groups and great progress towards proof of concept in industrial strains has been made [14][15][16][17][18]. Nevertheless, engineering industrial strains for the production of amylases at titers suitable in large scale applications still remains a major challenge [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Our research work is herein pertinent with the "Recent Advances" [7] in June 2020 addresses for starch-to-ethanol conversion have provided a platform for the development of raw starch consolidated bioprocessing (CBP) technologies. Several proof-of-concept studies identified improved enzyme combinations, alternative feedstocks and novel strains [8,9] for evaluation and application under fermentation conditions. However, further research efforts are required before this technology can be scaled-up to an industrial level.…”
Section: Introductionmentioning
confidence: 99%
“…In their review, different CBP approaches are defined and discussed, also highlighting the role of enzymes for a supplemented CBP process. Various achievements of amylolytic Saccharomyces cerevisiae strains [8,9] for CBP of raw starch and the remaining challenges that need to be tackled / pursued to bring yeast raw starch CBP to industrial realization are described in [7].…”
Section: Introductionmentioning
confidence: 99%